The Effect of Online Loan Application Ads for Families in Cinere District - Ichsan Nur Ramadhan; M. Bilal Abiyoso; Wahyunengsih (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2022)
This study is entitled The Effect of Online Loan Application Advertisements for Borrowing Families in Cinere District (Descriptive Study of the Effects of Journalism in the form of Online Loan Application Advertisements). The purpose of this study was to determine the effect of online loan advertisements on social media for borrowing families in the Cinere District. This study uses a descriptive method aimed at describing and analyzing so that the situation that becomes the research theme can be explained clearly. The population in this study is a family of researchers who have experience in making online loans. For the sampling of this research, the chosen technique is Non-Probability Sampling, a type of Purposive Sampling. Respondents are selected as members of the sample based on the researcher's considerations. In this study, the samples taken were three family members of each researcher who had experience doing online loans. The results showed that the influence of online loan advertisements appearing on social media succeeded in influencing informants to make loans. Both informants felt that online loan advertisements that often appeared on social media encouraged them to take loans. While one other informant felt that the influence of online loan advertisements on social media was less effective for elderly families due to limited knowledge about technology (technological gaps) so they preferred to borrow from banks or friends of the informants.